Analysis of mobile users' perception towards SMS voting - Sin, N.K.; Sulaiman, A.; Zolait, A.H.S. (2008)

(untitled)
Voting through Short Message Service (SMS) technology is fast and reliable as the mobile technology in Malaysia is quite advanced. Most of the SMS voting mechanism is easily understood by the public. There is no need to explain the voting process in detail as almost 80% of the mobile users know how to use the SMS service. SMS voting is just another way of sending a vote to the recipient by using short code instead of using a normal mobile number. SMS voting provides a useful, secure and reliable process as mobile users are informed of the charges incurred and receive a return SMS to acknowledge that their SMS vote has been received. The objective of this study is to study the characteristics of SMS voting adopters in terms of demographic factors as well as to explore the mobile users' perception towards SMS voting. A survey using questionnaires was conducted to gain information and opinions from a convenience sample of 300 Malaysian mobile users regarding their perceptions on using SMS to vote. The findings revealed that approximately two-thirds of the Malay respondents use SMS voting. most mobile users in the sample are single and female, and that mobile users like to send their votes using SMS. There is a significant difference between the usage of SMS voting among female respondents. Of the respondents 80 per cent perceive that the ease of use factor has greatly influenced mobile users in using SMS for voting purposes.